Collective action and civil society : disability advocacy in EU decision-making - Coveney, Claudia Harris (Emerald points., 2024)
Disabled people have played a key role in reshaping EU governance, leveraging times of reform to enhance their societal and legislative standing. In Collective Action and Civil Society: Disability Advocacy in EU Decision-Making, author Claudia Harris Coveney spotlights the European Disabled People's Movement (EDPM), examining its pivotal role and collective action within EU governance. Diving into the intricate relationship between civil society organizations (CSOs), social movements, and EU governance, chapters explore how certain organizations come to represent social movements within governance, and the resulting impact on policy and decision-making. Critically analysing the role of CSOs in decision-making processes, the author explores their function with other stakeholders and interest groups, and evaluates the challenges and opportunities presented by governance frameworks. Her work scrutinizes the concept of hegemony, how social movements negotiate existing power structures, and the conditions under which this can lead to counter-hegemonic change. Concluding with suggestions for a classification of different types of campaigns and a plan for future action, Coveney envisions the future of group initiatives, considering the changing landscape of political power, its distribution among stakeholders, and the evolving role of community groups. Unpacking the dynamics at play between CSOs, social movements, and governance in the European context, Collective Action and Civil Society offers an essential understanding of the potential for social change at a time of social turbulence.